2020
DOI: 10.4103/2045-9912.279982
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function dependence on carbon monoxide

Abstract: Nitric oxide, studied to evaluate its role in cardiovascular physiology, has cardioprotective and therapeutic effects in cellular signaling, mitochondrial function, and in regulating inflammatory processes. Heme oxygenase (major role in catabolism of heme into biliverdin, carbon monoxide (CO), and iron) has similar effects as well. CO has been suggested as the molecule that is responsible for many of the above mentioned cytoprotective and therapeutic pathways as CO is a signaling molecule in the control of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 66 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…CO is also a signal molecule that controls physiological functions and regulates inflammation. [ 207 ] This is counterintuitive because CO, known as a cell asphyxiant, binds to hemoglobin and reduces the unloading of oxygen in all tissues. However, CO is commonly produced in vivo and has cytoprotective properties associated with cellular stress, including in the heart.…”
Section: Injectable Hydrogel‐based Biomaterials To Reduce Inflammatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…CO is also a signal molecule that controls physiological functions and regulates inflammation. [ 207 ] This is counterintuitive because CO, known as a cell asphyxiant, binds to hemoglobin and reduces the unloading of oxygen in all tissues. However, CO is commonly produced in vivo and has cytoprotective properties associated with cellular stress, including in the heart.…”
Section: Injectable Hydrogel‐based Biomaterials To Reduce Inflammatio...mentioning
confidence: 99%
“…[ 208 ] In addition, CO, as an antioxidant and mitochondrial uncoupling factor, limits the production of H 2 O 2 . Meanwhile, CO may have a longer action time and distance compared to NO and H 2 S. [ 207 ] Therefore, CO delivery may be more suitable for inflammation regulation and disease treatment. The production of cardiovascular CO under basal conditions is continuous, and it increases with the upregulation of heme oxygenase (HO).…”
Section: Injectable Hydrogel‐based Biomaterials To Reduce Inflammatio...mentioning
confidence: 99%
“…The endogenous H 2 S has been found to have impact on the activity of K AT P channels in the smooth muscle and endothelial cells of blood vessels, where the intensity of the K + currents of incoming rectification enhanced by H 2 S and decreased by cystathionine gamma-lyase and cystathionine beta-synthase [22]. Unfortunately, there are no electrophysiological data confirming involvement of H 2 S into L-type CaV Inhibition of pore-forming subunit CaV cardiac L-type Ca 2+ channels Protection of cells from ischemic and reperfusion damages [55,210] the direct regulation of mitoK AT P channels. However, there are studies that support indirect participation of H 2 S, when using hydrogen sulfide donors, in the regulation of mitoK AT P channels and muscle cells of the CVS.…”
Section: Energy-producing Function Of Mitochondria and H 2 Smentioning
confidence: 99%
“…For example, BK Ca channels play an important role in the mechanism of the cardioprotective effect of H 2 S on cardiomyocytes during hypoxia, but they are also activated in response to the stimulation of CM by endogenous CO. Jaggar et al [208,209] found that CO regulates these channels by binding to reduced heme. Activators of BK Ca channels may have a protective effect on the CVS cells and vascular resistance during hypoxia and I/R [210]. NO is also a trigger molecule for the activation of BK Ca channels but increases their activity indirectly through PKG and PKA-related pathways [211].…”
Section: Interactions Of H 2 S No and Co In The Cardiovascular System During Hypoxiamentioning
confidence: 99%
“…Carbon monoxide (CO) is regarded as poisonous because of its high affinity for hemoglobin that rapidly increases carboxyhemoglobin to toxic levels that compromise O 2 delivery to the tissues. On the contrary, CO is constantly produced in the body and exerts vasoactive, antiproliferative, antioxidant, anti-inflammatory, and antiapoptotic effects and significantly contributes to cell protection, including the heart, and has been assessed for its cytoprotective and cytotherapeutic properties [6]. A previous report demonstrated that a high-pressure gas (HPG) preservation method using a mixture of CO and O 2 gases successfully resuscitated extracted rat hearts after 48 h of preservation [7].…”
Section: Introductionmentioning
confidence: 99%